Dynamic Microsimulation Model of Impoverishment Among Elderly Women in Japan - Inagaki, Seiichi (Frontiers in Physics, 2018)
The increasing poverty rate for elderly women is a growing concern in Japan and is generally due to their lifestyle changes and the public pension system based on the pre-1980s (old) lifestyle. At that time, women were expected to get married and become homemakers. Therefore, the public pension system is generous for married women and widows but not for never-married and divorced women. Using a dynamic microsimulation model, the Integrated Analytical Model for Household Simulation (INAHSIM), previous research has shown that poverty rates for elderly people will increase significantly in the future due to changes in nuptiality behavior after the 1980s. However, this approach is an indirect method, and the mechanism of impoverishment remains unclear. This study uses the same dynamic microsimulation model but attempts a more direct approach to interpret the effects of these behavioral changes on poverty rates for elderly women. Specifically, under the baseline scenario, it makes future projections on key distributions related to poverty by marital status and illustrates how they will face the poverty problem. It shows the future projections of (1) the distribution of pension amounts by gender and marital status, (2) poverty rates for elderly women by marital status, and (3) poverty rates for elderly people by gender. After the 1980s in Japan, the marriage rate decreased and the divorce rate increased significantly. Nevertheless, society still suffers from wage inequality between men and women. As a result, the number of never-married or divorced women will increase and these women will receive poor pension benefits due to an unfavorable public pension system. In addition, they have a higher risk of living in a single-person household because they have no or very few children. In the end, they will face the risk of poverty and raise the overall poverty rate.